Building Excellent Performance: The Role of Work Ethic and Discipline - Casmita Widodo; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to examine the influence of work ethic and work discipline on the performance of employees at the Civil Service Police Unit of Karawang Regency. The research employs a quantitative method using a survey approach. The sample consists of the entire population of 70 employees from the Civil Service Police Unit of Karawang Regency. Primary data were collected and analyzed using multiple regression analysis with SPSS 26.0. The results show that the work ethic of the employees is rated very highly. Similarly, their work discipline is also categorized as very good. Employee performance is assessed as good overall. Simultaneously, work ethic and work discipline have a significant influence on employee performance. Partially, work ethic has a significant impact on employee performance, and work discipline also shows a positive and significant effect.